Analysis of Teaching Materials for Social Studies Subject Matter Sub-Material of Economic Activity in Elementary School - Wahyudi, Achmad Basari Eko; Maigina, Ain (Universitas Sebelas Maret, 2022)
This study aim to describe the results of the analysis of teaching materials in 5th grades of elementary school, especially for the content of social studies subject, the economic activity sub-material. The research method used is a type of qualitative research with a descriptive qualitative research approach. The type of data used is qualitative data obtained from the responses of teacher as user of teaching materials, as well as observational studies of the school curriculum and documents of teaching materials used. Data collection techniques in this study used three techniques to obtain data, namely interview, observation and documentation techniques. the research instrument used is a list of structured questions related to research. The procedure for this research is divided into three stages including the preparation stage, the kalitengkek elementary schools in purworejo regency in accordance with the curriculum and learning objectives. The material is presented based on integrated thematic approach. In general, the presentation of social studies material especially on economic activity, is still lacking in accommodating students to have the ability to build economic activity concept from beginning and does not support the development of student economic activity skills. In addition, through the analysis of special social studies teaching materials, this economic activity can provide a reference for school and teachers to be able to further improve the quality of teaching materials by paying attention to learning aspects and the needs of students.